Influence of dielectric, Electro-Optic Kerr Effect and spectroscopic characterisation on polar–polar binary liquid mixture. (2nd January 2022) - Deshmukh, Snehal; Mohod, Ajay; Pattebahadur, Kanchan; Patil, Sunil; Kumbharkhane, Ashok; Khirade, Prakash
ABSTRACT: Complex dielectric spectra of the binary mixture of benzonitrile (BNZ) with acetophenone (ACPH) have been carried out at 11 different concentrations in the frequency range of 10 MHz to 40 GHz at four different temperatures (10°C, 15°C, 20°C and 25°C) using Time Domain Reflectometry technique. Static dielectric constant (ε0 ), relaxation time (τ) are obtained for above mentioned temperatures using nonlinear least squares fit method and density and refractive index are obtained at room temperature (25°C). These parameters are used to calculate the excess static dielectric constant (ε0 E ) and excess inverse relaxation time (1/τ) E, excess molar volume (Vm E ), effective Kirkwood correlation factor (g eff ), Bruggeman factor (fB ) and thermodynamic parameters such as enthalpy and entropy of activation of BNZ-ACPH mixture. Static dielectric constant decreases with increasing temperature and increasing concentration of ACPH in BNZ. The deviance in the excess parameters shows the strength of the molecular interactions and the presence of intermolecular interaction between unlike molecules. The measurement of Kerr constant (B) of the binary mixture of BNZ-ACPH have been reported for the wavelengths 632.8 nm and 512 nm for 5 different concentrations at room temperature using Electro-Optic Kerr Effect method. The change in the Kerr constant was observed for the different concentrations associated with the pure liquids. This deviation shows the non-additive behaviour and which is in good agreement with the dielectric parameters of the system under study. Also, the FTIR spectra have been obtained of BNZ-ACPH mixture to have a good agreement with the dielectric study.